Darna - Viva Films (Firm). ([Pasig City] Viva Films, 2005)
One fateful night, Narda and Ding witness a falling star. Driven by their curiosity, they approach it and they find a stone which unknown to them will change their lives forever. The magical stone gives Narda the power to be Darna. Darna meanwhile is a superhero who fights the satanic forces headed by Dominico Lipolito who disguises himself as a philanthropist. In his visit to the country Dominico recruits renowned fashion icon Valentina and public school teacher Purita Consunji to help him in his mission to spread evil. But one day, they attack a children's camp which unmask them and their true purpose of propagating harm and chaos. They also hypnotize Darna and entice her to promulgate their cause. Will evil finally rule?
VCD
Mars Ravelo
Nanette Medved
Keywords: Feature films